2017
DOI: 10.18203/2320-6012.ijrms20170625
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of acute subdural haematoma – a level I trauma care centre experience

Abstract: Background: Acute subdural hematoma is the most common type of traumatic intra cranial hematoma accounting for 24% cases of severe head injuries and caries highest mortality. The aim of this study is to analyse the clinical spectrum, and to evaluate the postoperative outcome.Methods: This is a prospective observational Study which included 150 patients  admitted  in King George hospital, Andhra Medical College, Visakhapatnam, India over the past two years (01st August 2013 to 30th August 2015) with head injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The differences between two groups were statistically significant (p<0.05). Prahaladu et al 9 obtained in their study that when post traumatic seizures were present the mortality was 35%, and when they were not present the mortality is 18.18%. Which were closely related with this study.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The differences between two groups were statistically significant (p<0.05). Prahaladu et al 9 obtained in their study that when post traumatic seizures were present the mortality was 35%, and when they were not present the mortality is 18.18%. Which were closely related with this study.…”
Section: Resultsmentioning
confidence: 95%
“…In this present study, it was observed that 63.0% and 64.3% of the patient's age belonged to 21 to 40 years in DC with MDS and CT with DT group respective, which were almost alike between two groups (p>0.05). Prahaladu et al 9 showed the maximum (63.0%) patients suffering from ASDH were in these group of 20 to40 years with male predominance (73.0%).Also Bhat et al 10 showed the comparative results of the multi-dural stabs and the open-dural flap revealed similar age distribution in both the groups, where nearly two third patients (65%) were in the age group of 21-40 years both from case as well as control groups, which is consistent with the current study. In this current study, it was observed that 85.7% patients of DC with MDS group and 78.6% patients of CT with DT group were male.…”
Section: Resultsmentioning
confidence: 99%
“…This hematoma can occur through three mechanisms, namely damage to parenchymal wound bleeding, cortical vessel surface, and tearing of the venous bridge from the cortex to the dural venous sinus. The clinical presentation of an acute subdural hematoma is a gradual change in the level of consciousness of a head injury patient, pupillary changes, increased restlessness, and hemiparesis indicating the side of the lesion (Prahaladu et al, 2017).…”
Section: Etiologymentioning
confidence: 99%
“…The clinical features of an acute subdural hematoma are a continuous decrease in level of consciousness, increased anxiety, pupillary changes and hemiparesis indicating the side of the lesion (Prahaladu et al, 2017). The most prominent area for hematoma formation is in the temporal region, followed by the frontal region, with the most well-known trigger being tearing of the central meningeal supply line.…”
Section: Hematoma Factors Affect the Prognostic Of Head Injurymentioning
confidence: 99%
“…Mortality ranges from 30% to 90%. 1 The possible mechanisms of injury leading to subdural haematoma include trauma, rupture of cortical bridging veins, damage to the surface cortical vasculature, bleeding from underlying injury to the brain parenchyma, intracranial hypotension and defective anticoagulation, among which trauma is the most common cause in children. Various factors related to a poor outcome in such patients include low Glasgow Coma Scale (GCS) score on admission, sluggishly reactive pupils, hypotension and bilaterality of the haematoma.…”
Section: Introductionmentioning
confidence: 99%